Estimation of Some Biomarkers and Cholesterol / HDL Ratio to Predict the Risk of Cardiovascular Disease in Rheumatoid Arthritis - Jabbar, Enas Abdul Kareem; Al-Rumaidh, Shaymaa Z.; Jouda, Jamela (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Rheumatoid arthritis (AR) is one of the chronic diseases resulting in many complications such as cardiovascular disease (CVD). Any change in the lipid profiles and myocardial markers indicates cardiovascular disease risk, so this study is designed to monitor the pattern of lipid profiles and myocardial markers in newly diagnosed RA patients. Blood samples were collected from 70 Iraqi patients newly diagnosed with rheumatoid arthritis (male and female) and 30 healthy served as control. These individuals were aged 35-65 years. The serum samples were obtained to determine myocardial markers; included troponin, creatinine kinase (CK), lactate dehydrogenase (LDH), and glutamic oxaloacetic transaminase GOT; and lipid profiles; such as cholesterol, triglyceride, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very-low-density lipoprotein (VLDL); using a kit from Roch (Germany), measured automatically with Minividas, Biomerieux (France). No differences between levels of all lipid profiles and myocardial markers in newly diagnosed RA patients compared with the healthy group were found as well as they were within the normal values, but interestingly, the cholesterol/HDL ratio increased significantly in RA patients comparing with healthy, so it could conclude that the risk of CVD could be increase also among the newly diagnosed of RA patients. Moreover, the cholesterol/HDL ratio should be probably included in a model to predict the risk of cardiovascular disease for RA in addition to the gender, age at the disease onset, and severity markers of disease.